Electromagnetic field effects on Y-meson dissociation in PbPb collisions at LHC energies - Hölck, Johannes; Wolschin, Georg (The European physical journal. A, Hadrons and nuclei, 2017)
We investigate the effect of the electromagnetic field generated in relativistic heavy-ion collisions on the dissociation of ΥΥ mesons. The electromagnetic field is calculated using a simple model which characterizes the emerging quark-gluon plasma (QGP) by its conductivity only. A numerical estimate of the field strength experienced by ΥΥ mesons embedded in the expanding QGP and its consequences on the ΥΥ dissociation is made. The electromagnetic field effects prove to be negligible compared to the established strong-interaction suppression mechanisms.
Gesehen am 25.04.2018